2009
DOI: 10.1111/j.1365-2095.2008.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the mechanical characteristics of faecal waste in rainbow trout: the influence of fish size and treatment with a non-starch polysaccharide (guar gum)

Abstract: This study (3 × 2 randomized factorial design) describes differences in the mechanical properties of faeces from rainbow trout of three size classes (small ≈40 g, mid‐size ≈150 g, large ≈650 g) and assesses the effects of a non‐starch polysaccharide binder (guar gum). Observations made at the macroscopic level were reinforced by rheological measurements of viscosity and elastic modulus. Mid‐sized fish excreted mechanically the most stable faeces, roughly twice as stable as those of small fish and three times m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 59 publications
4
46
0
Order By: Relevance
“…HY groups showed better growth and the fish with higher body weight showed worse fecal viscosity. This result was in line with study on rainbow trout (Brinker, 2009). …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…HY groups showed better growth and the fish with higher body weight showed worse fecal viscosity. This result was in line with study on rainbow trout (Brinker, 2009). …”
Section: Discussionsupporting
confidence: 94%
“…There also existed studies with no such dependency (Chen et al, 1993;Merino et al, 2007). Differences among fecal properties may be the results of the changes in digestive physiology of fish or the composition of the diets or a combination of them (Brinker, 2009). Simultaneously, fish digestive physiology is related to fish size and dietary composition (Guillaume et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have evaluated the addition of guar gum to fish diets, yet most have only observed the physical attributes of the feces (Amirkolaie et al, 2005;Brinker, 2007Brinker, , 2009Brinker and Reiter, 2012), nutrient digestibility (Leenhouwers et al, 2006), oxidative status, gastrointestinal tract morphology (Enes et al, 2012), and the effects on glucose and lipid metabolism (Enes et al, 2013). However, the mechanisms by which guar gum acts on body composition and modulates the microbial community in the tract remain uncertain.…”
Section: Introductionmentioning
confidence: 97%
“…The increase in digesta viscosity may also be responsible for impairment of macronutrient digestibility, thus leading to growth and feed efficiency depression. Inclusion of small amounts of guar gum (0.3 %) in rainbow trout Oncorhynchus mykiss diets enhanced feces stability in water, indicating that soluble NSPs may improve processing of fecal wastes in this species (Brinker et al, 2005and Brinker 2007, 2009). On the contrary, in the Nile tilapia Oreochromis niloticus, guar gum reduced feces stability due to its high water-binding capacity, thus not acting as appropriate feces binder in this species (Amirkolaie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%